(untitled) (The Review of Diabetic Studies, 2023)
Cellular microenvironment is known to play a critical role in the maintenance of human bone marrow-derived mesenchymal stem cells (BM-MSCs). It was uncertain whether BM-MSCs obtained from a ‘diabetic milieu’ (dBM-MSCs) offer the same regenerative potential as those obtained from healthy (non-diabetic) individuals (hBM-MSCs). To investigate the effect of diabetic microenvironment on human BMMSCs, we isolated and characterized these cells from diabetic patients (dBM-MSCs). We found that dBM-MSCs expressed mesenchymal markers such as vimentin, smooth muscle actin, nestin, fibronectin, CD29, CD44, CD73, CD90, and CD105. These cells also exhibited multilineage differentiation potential, as evident from the generation of adipocytes, osteocytes, and chondrocytes when exposed to lineage specific differentiation media. Although the cells were similar to hBM-MSCs, 6% (3/54) of dBM-MSCs expressed proinsulin/C-peptide. Emanating from the diabetic microenvironmental milieu, we analyzed whether in vitro reprogramming could afford the maturation of the islet-like clusters (ICAs) derived from dBM-MSCs. Upon mimicking the diabetic hyperglycemic niche and the supplementation of fetal pancreatic extract, to differentiate dBM-MSCs into pancreatic lineage in vitro, we observed rapid differentiation and maturation of dBM-MSCs into islet-like cell aggregates. Thus, our study demonstrated that diabetic hyperglycemic microenvironmental milieu plays a major role in inducing the differentiation of human BM-MSCs in vivo and in vitro.